The law regulating rural hospitality: A legal analysis of agricamping in Italy and selected EU Member States - Tedioli, Francesco (Przegląd Prawa Rolnego, 2025)
This article explores the legal framework of farm-based camping (agricampeggio) in Italy, analysing its classification as an agricultural activity and the associated regulatory, planning, environmental, and tax implications. Drawing on national and regional legislation, administrative practice and case law, it highlights the legal fragmentation and risks of misclassification. A comparative overview of selected EU Member States (France, Germany, and Spain) provides additional insights. The article concludes with recommendations for a more coherent and unified legal approach to rural hospitality within multifunctional agriculture.